A retrospective outcomes study 25-gauge 10,000 CPM beveled-tip and 25-gauge flat-tip microincision vitrectomy for proliferative diabetic retinopathy treatment - Han, Guangjie; Zhai, Jianwei; Huang, Hongbo; He, Limei; Wei, Heruo; Wei, Lirong; Wang, Huanyan (Frontiers in Medicine, 2025)
BackgroundTo evaluate the therapeutic efficacy and safety of 25-gauge (25G) 10,000 cpm (10K) beveled-tip microincision vitrectomy (MIVS) versus 25-gauge (25G) flat-tip MIVS in managing proliferative diabetic retinopathy (PDR).MethodsThis retrospective study involved 60 eyes with proliferative diabetic retinopathy (PDR) from 60 patients, all requiring epiretinal membrane removal. The patients were assigned to either the 25G 10K cpm beveled-tip MIVS group or the 25G flat-tip MIVS group. Surgical outcomes, including membrane removal efficiency, vitrectomy probe (VP) and microforceps exchanges, total procedure duration, vitrectomy time, and intraoperative complications, were documented. Best-corrected visual acuity (BCVA), intraocular pressure (IOP), and postoperative complications were assessed during a 6-month follow-up period.ResultsFifty-eight eyes (from 58 patients) completed follow-up, including 30 eyes in the 25G 10K cpm beveled-tip group and 28 eyes in the 25G flat-tip group. During surgery, the 25G 10k cpm beveled-tip group demonstrated more effective membrane cutting (p = 0.001) and required fewer exchanges between the vitrectomy probe and microforceps (p = 0.001). The total surgery time and vitrectomy time were both reduced in this group (p = 0.001 and p = 0.001, respectively). Additionally, fewer intraoperative hemostasis maneuvers were needed in the 25G 10K cpm beveled-tip group. All follow-up outcomes indicated no significant differences between the two groups.ConclusionIn the surgical treatment of PDR, the 25G 10K cpm beveled-tip MIVS group showed no statistically significant difference compared to conventional 25G flat-tip MIVS in terms of visual acuity improvement and postoperative intraocular pressure. However, the former demonstrated advantages such as reduced surgical time, decreased intraoperative use of electrocoagulation, and fewer instrument exchanges within the eye, providing robust evidence for its efficacy in PDR surgical management.